THE CORRELATION LEVELS FAMILIES TO STUDENT LEARNING ACHIEVEMENTS IN GRADE PRIMARY AL AZHAR BEJI – SURABAYA - Nuryasana, Endang (Jurnal Pena Karakter (Jurnal Pendidikan Anak dan Karakter), 2018)
Education parents are very affecting against student learning achievements in following their experiences in the out of school .Parents educated ranging from elementary school , junior high school , senior high school , to university .Synthesis a problem in this research how can influence the level of education of the results of the family to study for students in the class v primary school al azhar beji throughout surabaya ? the purpose of this research is to know the influence of the level of education of the results of the family to study for students in the class v primary school al azhar beji surabaya.metodologi used in this research is the methodology that was used in this research by using skoring on the level of education was continued by correlation against know learning achievements. The results of this research are (1) father's educational background. The value of the Sig (0.815) then Ho accepted. So these two variables was not significant (2) mother's educational background. The value of the Sig (0.722) then Ho accepted. So these two variables was not significant (3) education dad with a variable control of the education of the mother who shows little correlation kooefisien value (0.020). The value of the Sig (0.925)  Ho is admitted. So the relationship between the two variables with variables mother's Education was not significant.